Interfaith Marriage from the Perspective of Maqashid Al-Syari'ah Jasser Auda (Analysis of Decision Number 916/Pdt.P/2022/PN.Sby.) - Amin, Muhammad Nurfikri; Nasrullah, Nasrullah; Sj., Fadil (Mutawasith: Jurnal Hukum Islam, 2023)
Interfaith marriage has emerged as a significant and complex issue within Indonesian society, encompassing academic, social, and religious dimensions. This research aims to explore and address the academic, social, and religious challenges posed by interfaith marriages in Indonesia, referencing both previous research findings and a recent court decision. In the academic sphere, the study delves into the legal aspects, rights, obligations, and judicial implications of interfaith marriages. It sheds light on how Indonesian law regulates such unions. The recent Surabaya District Court's Decision Number 916/Pdt.P/2022/PN.Sby, permitting an interfaith marriage, is analyzed through the lens of Jasser Auda's Maqasid al-Shariah theory, which emphasizes social welfare, justice, and human rights in Islamic law. The decision reflects a shift from classical to contemporary Maqasid, focusing on human development and rights, particularly the freedom to marry across religious boundaries. This study contributes to a comprehensive understanding of interfaith marriage in Indonesia, emphasizing a contemporary interpretation of Islamic law and universal human rights, ultimately working towards harmony and inclusivity in this diverse society.